Answer:
This isn’t really a valid equation, so I’m guessing you forgot to type something.
Step-by-step explanation:
That is so cool, thanks for the trick idea.
X = 0 ; y = 10 ; 10 = a(0) + b(0) + c
c = 10
x=2 ; y = 15 ; 15 = a(4) + b(2) + 10 ; 5 = 4a+2b
x=4 ; y=18 ; 18 = a(16) + b(4) + 10 ; 8 = 16a + 4b
2(5) = (4a+2b)2
-
<u> 8 = 16a + 4b
</u> 2 = -8a
a = -0.25
b = 2
y = (1/4)x^2 + 2x + 10 ; 4y = x^2 + 8x + 40
Answer:
i think it is 6 but not sure
Step-by-step explanation:
Center: (-5,-6)
Radius: 39
How to do it
Complete the square for
y
2
+
12
y
y
2
+
12
y
.
(
y
+
6
)
2
−
36
(
y
+
6
)
2
-
36
Substitute
(
y
+
6
)
2
−
36
(
y
+
6
)
2
-
36
for
y
2
+
12
y
y
2
+
12
y
in the equation
(
x
+
5
)
2
+
y
2
+
12
y
=
3
(
x
+
5
)
2
+
y
2
+
12
y
=
3
.
(
x
+
5
)
2
+
(
y
+
6
)
2
−
36
=
3
(
x
+
5
)
2
+
(
y
+
6
)
2
-
36
=
3
Move
−
36
-
36
to the right side of the equation by adding
36
36
to both sides.
(
x
+
5
)
2
+
(
y
+
6
)
2
=
3
+
36
(
x
+
5
)
2
+
(
y
+
6
)
2
=
3
+
36
Add
3
3
and
36
36
.
(
x
+
5
)
2
+
(
y
+
6
)
2
=
39
(
x
+
5
)
2
+
(
y
+
6
)
2
=
39
This is the form of a circle. Use this form to determine the center and radius of the circle.